Determinants of health insurance coverage among women in Mauritania: a multilevel analysis - Robert Kokou Dowou; Gideon Awenabisa Atanuriba; Leticia Akua Adzigbli; Samuel Kwaku Balame; Issifu Tahidu; Juliet Aggrey-Korsah; Richard Gyan Aboagye (BMC, 2024)
Abstract Background Health insurance has been documented as one of the primary methods of financing healthcare for Sustainable Development Goals (SDGs) by 2030. Yet, there is a dearth of evidence on the determinants of health insurance coverage among women in Mauritania. We examine the factors associated with health insurance coverage among women in Mauritania using a nationally representative survey dataset. Methods We analyzed secondary data from the 2019-2021 Mauritania Demographic and Health Survey. A weighted sample of 15,714 women of reproductive age (15-49 years) was included in the study. Multilevel regression analysis was used to examined the factors associated with health insurance coverage. The results were presented using an adjusted odds ratio (aOR) with a 95% confidence interval (CI). Results The coverage of health insurance among women was 8.7%. The majority of the women subscribed to social security health insurance (7.6%). Women aged 35 years and above [aOR = 1.54; 95% CI = 1.24, 1.92] were more likely to be covered by health insurance relative to those aged 15-24. The likelihood of being covered by health insurance increased with increasing level of education with the highest odds among women with higher education [aOR = 6.09; 95% CI = 3.93, 9.42]. Women in the richest wealth index households [aOR = 22.12; 95% CI = 9.52, 51.41] and those with grand parity [aOR = 2.16; 95% CI = 1.62, 2.87] had the highest odds of being covered by health insurance. Women who were working, those who watched television, and those who used the internet were more likely to be covered by health insurance relative to their counterparts who were not working, those who did not watch television, and those who did not use the internet. Women residing in Tiris zemour et Inchiri [aOR = 3.60; 95%CI = 1.60, 8.10], Tagant (aOR = 3.74; 95% CI = 1.61, 8.68], and Adrar [aOR = 2.76; 95% CI = 1.36, 5.61] regions were more likely to be covered by health insurance compared with those from Hodh Echargui. Conclusion Health insurance coverage among the women in our study was low. Achieving the SDG targets of ensuring universal health coverage and lowering maternal mortality to less than 70 deaths per 100,000 live births requires the implementation of interventions to increase health insurance coverage, taking into consideration the identified factors in the study. We recommend effective public education and awareness creation on the importance of being covered by health insurance by leveraging television and internet platforms. Also, interventions to increase health insurance coverage should consider younger women and those in rural areas.